2013
DOI: 10.3390/nu5062093
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Viscosity and Fermentability of Dietary Fibers on Satiety- and Adiposity-Related Hormones in Rats

Abstract: Dietary fiber may contribute to satiety. This study examined the effect of two dietary fiber characteristics, small intestinal contents viscosity and large intestinal fermentability, on satiety-and adiposity-related hormones in rats. Diets contained fiber sources that were non-viscous, somewhat viscous, or highly viscous, and either highly fermentable or non-fermentable, in a 2 × 3 factorial design. In the fed state (2 h postprandial), rats fed non-fermentable fibers had significantly greater plasma GLP-1 conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 40 publications
(97 reference statements)
3
33
0
1
Order By: Relevance
“…The viscosity of KM and GG was higher than that of PHGG, but plasma GLP-1 and PYY concentrations in rats fed KM and GG were lower than that in rats fed PHGG. Schroeder et al [27] have reported that viscosity had no significant influence on plasma concentrations of GLP-1 and PYY.…”
Section: Discussionmentioning
confidence: 99%
“…The viscosity of KM and GG was higher than that of PHGG, but plasma GLP-1 and PYY concentrations in rats fed KM and GG were lower than that in rats fed PHGG. Schroeder et al [27] have reported that viscosity had no significant influence on plasma concentrations of GLP-1 and PYY.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of certain dietary fibers, including the prebiotic fiber oligofructose (OFS), increases the secretion of GLP-1 and PYY [6,7]. The endogenous release of GLP-1 and PYY-through changes in food intake-may be part of the reason why some dietary fibers improve physiologic health [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Para essa categoria, o "claim" descrito acima não é permitido no rótulo, e sim apenas a alegação "fonte de fibras" quando o mesmo fornece as mesmas 3 g.100 g -1 para alimentos sólidos e 1,5 g.100 mL -1 para líquidos. Caso apresente o dobro deste conteúdo é considerado um alimento com elevado teor de fibra alimentar, e pode apresentar no rótulo a denominação "rico em fibras alimentares" (BRASIL, 2012a) Fisiologicamente as fibras são consideradas substâncias de origem vegetal que auxiliam no aumento do volume do bolo fecal e diminuem o tempo do mesmo do transito intestinal (SCHROEDER, 2013). Elas pertencem a uma ampla categoria dos carboidratos, podendo ser fermentáveis ou não fermentáveis, ainda divididas quanto às suas características estruturais, em polissacarídeos estruturais e não estruturais (SAAD, 2006 …”
Section: Fibras Alimentaresunclassified